2008
DOI: 10.1002/ep.10295
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial neural networks to estimate wastewater treatment plant inlet biochemical oxygen demand

Abstract: Biochemical oxygen demand (BOD) has been shown to be an important variable in water quality management and planning. However, BOD is difficult to measure and needs longer time periods (5 days) to get results. Artificial neural networks (ANNs) are being used increasingly to predict and forecast water resource variables. The objective of this research was to develop an ANNs model to estimate daily BOD in the inlet of wastewater biochemical treatment plants. The plantscale data set (364 daily records of the year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 8 publications
4
50
1
2
Order By: Relevance
“…The accuracy of predictions is satisfactory, which is illustrated by the values of errors obtained (Tables 2-4). Although the parameters of computations fit to measurements (R, MAE, MAPE) received in this study were worse than those reported by Minsoo et al [5], Dogana et al [15], Verma and Kusiak [4] the models designed in this study can find practical applications. When the number of independent variables in the statistical models is limited to only wastewater inflow data, the models could be employed under failure conditions of the measurement system, or during the system overhaul.…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…The accuracy of predictions is satisfactory, which is illustrated by the values of errors obtained (Tables 2-4). Although the parameters of computations fit to measurements (R, MAE, MAPE) received in this study were worse than those reported by Minsoo et al [5], Dogana et al [15], Verma and Kusiak [4] the models designed in this study can find practical applications. When the number of independent variables in the statistical models is limited to only wastewater inflow data, the models could be employed under failure conditions of the measurement system, or during the system overhaul.…”
Section: Resultscontrasting
confidence: 49%
“…To predict BOD5, Abyaneh [3] relied on temperature, pH of influent wastewater, and TSS. Dogan et al [15] received a better fit (R = 0.92) of BOD5 simulation results to measurements than Abyaneh [3]. Additionally, the values of MAPE computed for COD prediction model are greater than those (MAPE = 7.35%) obtained by Minsoo et al [5] with the k-NN method.…”
Section: Resultsmentioning
confidence: 59%
“…Determinasyon katsayısı (R 2 ), ölçüm değerleri ile model tahminleri arasında doğrusal bir iliĢki olup olmadığını belirlemek amacıyla kullanılır. R 2 değeri 0 ile 1 arasında değiĢmekte ve bu değerin 1'e yaklaĢması model tahminleri ile ölçüm değerleri arasındaki bağımlılığın kuvvetli olduğu anlamına gelmektedir [33].…”
Section: Performans Kriterleri (Performance Criteria)unclassified
“…Moreover, the application of artificial neural network to spectrophotometric determination of challenging chemical substances is known to be very efficient [7]. The ANN model develops a mapping of the input and output variables, which can subsequently be used to predict as a function of suitable inputs making it very popular in handling various water quality problems [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%